Pendekatan Inovasi Dalam Proses Belajar Mengajar Untuk Mengatasi Minat Rendahnya Siswa Terhadap Pembalajran IPS - Muhammad Romahurmuzi F; Irna Firdausil Ma’wa; Isyroq ziyaul Haq; Lutfi Fadilatun Nisa; Achmad Wildan Alfaizin Utama; Syafira Hurinin; Nurdianti Nurdianti; Bagus Setiawan (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Social studies learning must be taught to students in a constructivist manner. There are 5 (five) methods that can be taught in social studies learning, including cooperative-based learning, design-based learning, inquiry-based learning, project-based learning, and problem-based learning. However, there are still many students who are less interested in social studies learning. Therefore, an innovative approach is needed in the teaching and learning process to overcome students' low interest in social studies learning. In the research conducted, innovative approaches in the teaching and learning process can increase students' interest in social studies learning. Some innovative approaches that can be done include the use of technology, integrated learning with activities outside the classroom, integrated learning with other subjects, and integrated learning with students' daily lives. With the right approach to innovation, it is expected that students' interest in social studies learning can increase and student learning outcomes can be better.